A scoping review on health education programs for improving Men's engagement with health services in low- and middle- income countries - Tafadzwa Dzinamarira; Desmond Kuupiel; Portia Vezi; Tivani Phosa Mashamba-Thompson (Elsevier, 2021)
Objectives: This study aimed to map evidence on health education programs (HEPs) for men engagement in health services in LMICs to guide future research. Study design: A scoping review was conducted. Methods: We searched Google Scholar, PubMed, EBSCOhost (CINAHL, MEDLINE, Health Source, Nursing, Academic Edition and Academic Search Complete) and WEB of Science electronic databases for publications from January 2000 to March 2019. We also searched Researchgate, the WHO library, and universities repositories for grey literature such as dissertations, theses, and reports. The search terms included "health," "education," "program," "men", with Boolean terms, AND and OR, being used to separate the keywords. Articles reporting evidence on HEPs for men aged 15 and older in LMICs and HEPs improving men's engagement in health services in LMICs published in any language between January 2000 to March 2019 were included in this review. We appraised included studies using the 2018 version of the Mixed Methods Appraisal Tool. We used thematic content analysis to extract emerging themes and presented a narrative account of the findings. Results: Database search retrieved 8905 eligible articles. Of these, only six studies met the inclusion criteria and were included for data extraction. All included studies reported evidence of health education for men engagement in health services. The total number of men reported in the studies was 4372 with an age range of 15-54. Included studies were conducted in Uganda, Kenya, Ghana, and Zimbabwe. Included studies presented evidence on HEPs for men engagement in health services. Two main themes emerged from thematic content analysis of included studies: mode of health delivery (the process of enabling men and boys to become involved in health services as patients/clients) and health benefits to men (to achieve better health outcomes). Conclusion: Our review revealed limited evidence of HEPs for men engagement in health service. Regardless of mode of health education delivery, notable health benefits to men were reported. We recommend implementation research on HEPs for men engagement in health services to better understand the social, cultural and economic influences in LMICs.